Analysis of Student Creativity Assessment Instruments: Supporting SDGs and MBKM in Higher Education - Rahyu Setiani; Widiasih Widiasih; Suparti Suparti; Dwikoranto Dwikoranto; Lindsay N. Bergsma (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aimed to produce a valid and reliable Creativity Assessment Instrument that can be used in learning. Students' low creative thinking ability and the unavailability of a Creativity Assessment Instrument to measure creativity in the science field of elementary school students are the background to this study. Method: The instrument was compiled through the following stages: potential and problems, data collection, product design, design validation, design revision, and valid and reliable final results. Data were collected using a validation sheet. Data from the validation results were then analyzed quantitatively descriptively and then compared with the validity criteria table that had been set. As a result, the creativity assessment instrument has been designed to measure creative thinking skills using descriptive questions. Results: Assessment of the material, construction, and language aspects showed high and reliable validity in the categories. This shows that the instrument can be used in the context of learning to measure student creativity effectively. There has been an increase in the development of creativity assessment instruments to measure students' creative thinking skills in elementary school science subjects, which were previously lacking but are now increasing due to this research. Novelty: For further development research, it is recommended that creativity assessment instruments have broader topics and are also equipped with Student Worksheets that can not only measure creative thinking skills but also measure the creative process and creative products.